Prevalence and Configuration of the Second Mesiobuccal Canal in the Permanent Maxillary First Molar in Jordanian Population Sample - Alsaket, Yousof M.; El-Ma’aita , Ahmad M.; Aqrabawi , Jamal; Alhadidi , Abeer (Iranian Endodontic Journal, 2020)
Introduction: Missing a root canal during endodontic treatment implicates the persistence of microbial infection within the root canal system. This study aims to evaluate the incidence and morphology of the second mesiobuccal canal in the maxillary first molars in the Jordanian population. Methods and Materials: Consecutive cone-beam computed tomography (CBCT) scans taken at Jordan University Hospital were assessed in this retrospective study. A total of 200 scans that were examined, 111 were included in this study. The scans that were included had to have a full view of the maxilla with at least one permanent maxillary first molar. The following data were collected: the presence of a second mesiobuccal canal, the configuration of the mesiobuccal canals, the status of the apical area and the mesiobuccal inter-orifice distance, if applicable. The prevalence and morphology of the second mesiobuccal canal was determined and its association with biological sex and right or left sidedness was measured using the Chi-Square test. Results: The prevalence of the second mesiobuccal canal in our sample of the Jordanian population was 87%, with the most common canal configuration being Vertucci type II. The average inter-orifice distance between first and second mesiobuccal canals was 1.9 ± 0.4 mm. Conclusion: This retrospective study is the first in Jordan to document the prevalence of the second mesiobuccal canal using CBCT, and it shows that the vast majority of teeth have a second mesiobuccal canal. The proper location and negotiation of this canal is of dire importance for endodontic therapy.